Pasar Segoro Campurejo - Nashihin, Muhammad; Korantalaga, Bayu Pratama; Qolbiyah, Shofwatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study explores the Segoro Campurejo Market as a representation of coastal epistemology that reflects the social, economic, cultural, and educational dynamics of coastal communities. The purpose of this study is to reveal the meaning of the shell revolution as a symbol of transformation and to examine the practice of tolerance education in the market as a space for multicultural interaction. Using a qualitative ethnographic approach through field observations, interviews, and documentation, this study shows that the market functions not only as an economic center but also as an arena for art, culture, and local wisdom. Symbols such as boats and nets indicate a deep connection with the lives of fishermen, while shells as a medium of exchange revive historical and symbolic values. Furthermore, the market becomes a place for social gatherings that bridges differences in age, status, and culture, thereby fostering harmony and tolerance. In conclusion, Segoro Campurejo Market illustrates local-based social harmony that offers insights for global coexistence